The role of emulsion properties and stability in vegetable oil uptake by regranulated cork sorbents - Ariana M. A. Pintor (2015)
BACKGROUNDThis work presents a novel approach to the understanding of electrostatic phenomena and sorbate-sorbent interactions in oil sorption. The study focuses on sorption of sunflower oil onto regranulated cork granules as promising natural sorbents. RESULTSIt was shown that lowering the pH caused neutralization of negative surface charge by the positive hydrogen ions, leading to a reduction in the negative value of -potential, and further destabilization of the emulsion, and an increase in oil and grease (O&G) uptake by cork granules. The effect of ionic strength was studied using a 3-level, 2-factor (3(2)) full factorial design with O&G removal efficiency as the response variable. Linear effects of NaCl concentration, pH, and their interaction were found to be statistically significant (P < 0.05). Higher salt concentrations enhanced O&G removal due to double layer compression. Kinetic and equilibrium studies showed that the sorption process could be well described by a mechanism of partitioning governed by the external film fluid resistance. CONCLUSIONIn the conditions of 0.2molL(-1) NaCl and pH 6, a mass transfer model adequately predicted oil removal of emulsions with approximately 140mgL(-1) O&G to values below discharge limits using 1.6gL(-1) of cork granules. (c) 2015 Society of Chemical Industry